Bioinsektisida berbasis tanaman dari Jatropha gossypiifolia dan urin sapi untuk pengendalian lalat kuda - Elisa Rainata Besin; I Putu Juli Sukariada; Putu Mira Puspitayani (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Bioinsecticides are natural compounds with toxic properties that can inhibit the growth and development of pests that affect crops and livestock. This study aimed to evaluate the effectiveness of a bioinsecticide formulation derived from red jatropha (Jatropha gossypiifolia) leaf extract combined with cattle urine against ectoparasites in cattle. The experiment was a completely randomized design (CRD) involving 200 flies, which were divided into four treatment groups with concentrations of 0%, 10%, 15%, and 20%, each replicated three times. The results demonstrated that the bioinsecticide formulation at a concentration of 20% had a significant effect on fly mortality compared to lower concentrations. These findings suggest that the combined use of 20 % red jatropha leaf extract and cattle urine is a promising and environmentally friendly alternative for controlling fly populations in cattle.